QUALITATIVE APPROACH IN INNOVATIVE LEARNING MODEL DEVELOPMENT: GROUNDED THEORY STUDY ON TEACHER PRACTICES - Zulfaida, Arini; Puspitasari, Ira (Four Son Scholarship, 2025)
Learning innovation is an important prerequisite for improving the quality of learning processes and outcomes in the 21st century education era. However, various studies show that innovations adopted mechanically from training or policies often fail because they are not connected to the real experiences of teachers. This study aims to develop a conceptual model of experience-based pedagogical innovation through a qualitative approach using grounded theory design. Data were obtained through in-depth interviews, classroom observations, and analysis of learning documents of teachers considered innovative, selected through purposive and theoretical sampling until data saturation was achieved. Analysis was conducted through open coding, axial coding, and selective coding using the constant comparative method. The findings show that pedagogical innovation emerges as a cyclical process that moves through the stages of awareness of change, design experimentation, reflection on action, and reconstruction of learning strategies. At the core of this process is the view that teachers produce pedagogical knowledge from their practical experiences, so that innovation is understood as a living model that continues to evolve according to the classroom context and the dynamics of the students. The resulting conceptual model positions teachers as practical theorists and learning as a reflective laboratory for the construction of educational knowledge. The implications of this study emphasize the need for teacher development programs based on practical reflection, policies that allow room for teacher creativity, and further research to test this model in different educational contexts. This research contributes theoretically to understanding learning innovation as an emergent and experience-based phenomenon, and practically to designing more relevant and sustainable learning quality improvement.